Perkembangan Ekonomi Dan Administrasi Pemerintahan Masa Dinasti Umayyah - Emi Hariyanti; Kholid Mawardi (Journal on Education, 2023)
The type of research used is literature research or literature study where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions. Literature research or literature research is research whose place of study is literature or literature. All Muslim regions speak one language, Arabic, as their official language. However, all cultural expressions were also expressed in Arabic then also non-Arabs began to participate in the building of "culture" and "civilization". The political history of the Islamic world is divided into three periods: first, the classical period (650-1250 AD); second, the Middle Ages (1250-1800 AD) and third, the modern period (1800s). The first period was the "Golden Age" of Islamic history. In the Golden Age it was often used as a reference and exemplary reference. Results and discussion In the economic field, real monetary policy was applied during the reign of the Umayyad Dynasty with printed money by Muawiyah bin Abi Sufyan. Abd al-Malik converted Byzantine and Persian currencies used in areas under Muslim rule. Furthermore, in the field of government administration, the change of leadership was arranged from one generation to the next, when Muawiya obliged all his people to declare allegiance to his son Yazid, he made the principle of nepotism the basis for the appointment of the caliph. This shows that Muawiya intended to emulate the Persian and Byzantine monarchies, i.e. the hereditary use of leadership.